Hubungan Dukungan Sosial Dengan Stres Akademik Siswa SMA Negeri 11 Ambon - Asrul Asrul; Sawal Mahaly; Muhamad Fadli (-, 2026)
This study aimed to examine the relationship between social support and academic stress among students at SMA Negeri 11 Ambon. The research employed a quantitative approach with a descriptive correlational design. The study population consisted of 1,514 students, while a sample of 316 respondents was determined using the Slovin formula with a 5% margin of error and selected through proportionate random sampling. Data were collected using a questionnaire that met the requirements of validity and reliability. Data analysis included descriptive statistics and Pearson product-moment correlation analysis. The findings showed that social support was predominantly in the high category, with 174 students (55.1%), followed by the moderate category with 109 students (34.5%) and the low category with 33 students (10.4%). Meanwhile, academic stress was predominantly in the moderate category, involving 168 students (53.2%), followed by the low category with 87 students (27.5%) and the high category with 61 students (19.3%). The correlation analysis revealed a strong and statistically significant relationship between social support and academic stress (r = -0.612; p 0.001). In other words, the higher the level of social support received from family, peers, teachers, and the school environment, the lower the students’ tendency to experience academic stress.